Mammographies The Cultural Discourses of Breast Cancer Narratives - DeShazer, Mary K. (University of Michigan Press, 2013)
While breast cancer continues to affect the lives of millions, contemporary writers and artists have responded to the ravages of the disease in creative expression. Mary K. DeShazer's book looks specifically at breast cancer memoirs and photographic narratives, a category she refers to as mammographies, signifying both the imaging technology by which most Western women discover they have this disease and the documentary imperatives that drive their written and visual accounts of it. Mammographies argues that breast cancer narratives of the past ten years differ from their predecessors in their bold address of previously neglected topics such as the link between cancer and environmental carcinogens, the ethics and efficacy of genetic testing and prophylactic mastectomy, and the shifting politics of prosthesis and reconstruction.